Digital Marketing Development Model through Digital Literacy Mediation to Improve SME's Performance - Ivonne Angelic Umboh; Vincent Didiek Wiet Aryanto (Media Ekonomi dan Manajemen, 2023)
The objective of this research is to undertake the digital literacy competence among the SME (Small and Medium Enterprises) actors and to answer the previous research evidence that digital literacy is still under study; therefore, digital literacy among the SMEs a cluster of MSME, natural dyes Batik Kebon Indah Bayat Klaten is used as location of this research. Method of the study was carried out by census to all members of cluster batik natural dyes in Bayat Kebon Indah Klaten. All 186 batik members were withdrawn as respondent of this study, the reason for withdrawing all cooperative member of Kebon Indah because they were engaged in digital marketing activities to promote their natural dyes batik products. The engagement in social media to promote their products was vulnerable to digital illiteracy exposures. Digital literacy is a mediating variable bridging the gap between digital marketing capability and SME business performance. The findings reveal that digital marketing capability has a significant impact on SME business performance, digital literacy has a considerable effect on SME's business performance, and digital literacy significantly impacts digital marketing capability. Implication of the study found out that digital literacy prevented the respondents to believe in hoax, several deceiver’s efforts of business deceptions, therefore digital literacy strengthened them to be cautious in managing their business.